Critiquing Workplace Learning Discourses: Participation and Continuity at Work - Billett, Stephen (Studies in the Education of Adults, 2002)
Although workplace learning is frequently characterized as informal, it usually involves structured, goal-directed, intentional activities. Instead, learning should be seen as interdependent between the individual and the social practice. Tensions arise between the need for continuity and work practices and individual needs to realize goals. (Contains 52 references.) (Author/SK)
Keywords: formation des adultes